2015
DOI: 10.1007/s00382-015-2904-7
|View full text |Cite
|
Sign up to set email alerts
|

Moisture dynamics of the northward and eastward propagating boreal summer intraseasonal oscillations: possible role of tropical Indo-west Pacific SST and circulation

Abstract: centre in other two categories. Thus the present study concludes that the difference in underlying SST and atmospheric circulation in tropical Indo-west Pacific oceanic regions encourage the differential propagation of BSISO convection through moisture dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Such an objective and systematic study has not yet emerged. Previous studies on BSISO diversity are either subjective (e.g., B. Wang & Rui, 1990) or not systematic (e.g., Pillai & Sahai, 2016, in that study the propagation directions are pre‐defined). This work attempts a systematic and objective description of BSISO propagation diversity and an in‐depth grasp of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an objective and systematic study has not yet emerged. Previous studies on BSISO diversity are either subjective (e.g., B. Wang & Rui, 1990) or not systematic (e.g., Pillai & Sahai, 2016, in that study the propagation directions are pre‐defined). This work attempts a systematic and objective description of BSISO propagation diversity and an in‐depth grasp of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical intraseasonal oscillation (ISO) exhibits pronounced seasonality (Madden, 1986; B. Wang & Rui, 1990). The boreal summer intraseasonal oscillation (BSISO), active mainly over the Indo‐Pacific warm pool region, is more complicated than its winter counterpart, the Madden‐Julian Oscillation (MJO) (Madden & Julian, 1971, 1972), due to the coexistence of equatorial eastward, off‐equatorial westward, and northward propagating low‐frequency modes and their interactions (Lau & Chan, 1986; Pillai & Sahai, 2016; B. Wang & Xie, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, an investigation on the characteristics of ISO over the AS and BoB would provide an insight on the problem. Earlier studies have shown that moisture advection, specifically advection of climatological moisture by the anomalous wind from the northwest Pacific, is the principal factor in initiating the active or break conditions over India (Annamalai, ; Pillai & Sahai, , ; Prasanna & Annamalai, ). Furthermore, moisture advection is found to lead rainfall by 8–9 days, whereas there is no lead‐lag between rainfall and moisture convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, possible causes for disparity between northwards propagation of MISO in the AGCMs simulations are considered. Studies (Ajayamohan et al, 2011; Pillai & Sahai 2014, 2016) proposed that the anomalous moisture advection plays a major role in the northwards migration of MISO convection from the equatorial IO to the Indian subcontinent. Hence, 30–60‐day filtered precipitation and horizontal moisture advection at each grid point is correlated at the different time lags with respect to a reference time series created by averaging the 30–60‐day filtered precipitation anomalies averaged over the IO.…”
Section: Discussion and Summarymentioning
confidence: 99%